Formation of glyco-functionalized interfaces for protein binding using polyphenolic glycoside. (June 2020) - Seto, Hirokazu; Harada, Mao; Nagaura, Hidenori; Taniguchi, Honoka; Murakami, Tatsuya; Kimura, Ichiro; Hirohashi, Yumiko; Shinto, Hiroyuki
Abstract: In this study, a polyphenolic glycoside (α-glucosyl rutin) was used to form glyco-functionalized interfaces for protein binding. α-Glucosyl rutin was coated onto precious metals, metal oxides, and synthetic polymers, including polyethylene and polytetrafluoroethylene with poor surface modifiability. The glyco-functionalized interfaces bound strongly and specifically to concanavalin A and Bauhinia purpurea lectin, which have different carbohydrate specificities. Competitive adsorption tests demonstrated that the binding sites for the abovementioned lectins were glucosyl and rhamnosyl residues, respectively. The glyco-functionalized interfaces maintained the protein binding ability after being stored in aqueous solution for 1 day and in air for 160 days. Once the glyco-functionalized interfaces were formed on gold, silicon dioxide, polystyrene, and polytetrafluoroethylene using α-glucosyl rutin, all the glyco-functionalized interfaces bound to concanavalin A rather than peanut agglutinin. Graphical abstract: Image 1 Highlights: α-Glucosyl rutin was used to form glyco-functionalized interfaces. Glyco-functionalized interfaces could be formed on various surface materials. Glyco-functionalized interfaces exhibited strong bindability to particular proteins. Adsorption of protein to the interfaces was observed on various surface materials.